An Enhanced Variant Designed From DLP4 Cationic Peptide Against Staphylococcus aureus CVCC 546 - Li, Bing; Yang, Na; Wang, Xiumin; Hao, Ya; Mao, Ruoyu; Li, Zhanzhan; Wang, Zhenlong; Teng, Da; Wang, Jianhua (Frontiers in Microbiology, 2020)
Insect defensins are promising candidates for the development of potent antimicrobials against antibiotic-resistant Staphylococcus aureus (S. aureus). An insect defensin DLP4, isolated from the hemolymph of Hermetia illucens larvae, showed low antimicrobial activity against Gram-positive (G+) pathogens and high cytotoxicity, which limited its effective therapeutic application. To obtain more potent and low cytotoxicity molecules, a series of peptides were designed based on the DLP4 template by changing the conservative site, secondary structure, charge, or hydrophobicity. Among them, a variant designated as ID13, exhibited strong antibacterial activity at low MICs values of 4-8 μg/mL to G+ pathogens (S. aureus: 4 μg/mL, Staphylococcus epidermidis: 8 μg/mL, Streptococcus pneumoniae: 4 μg/mL, Streptococcus suis: 4 μg/mL), which were lower than those of DLP4 (S. aureus: 16 μg/mL, S. epidermidis: 64 μg/mL, S. pneumoniae: 32 μg/mL, S. suis: 16 μg/mL), and cytotoxicity of ID13 (71.4% viability) was less than that of DLP4 (63.8% viability). ID13 could penetrate and destroy the cell membrane of S. aureus CVCC 546, resulting in an increase in the potassium ion leakage; it bound to genomic DNA (gDNA) and lead to the change of gDNA conformation. After treatment with ID13, perforated, wrinkled, and collapsed S. aureus CVCC 546 cells were observed in electron microscopy. Additionally, ID13 killed over 99.99% of S. aureus within 1 h, 2×MIC of ID13 induced a postantibiotic effect (PAE) of 12.78±0.28 h, and 10 mg/kg ID13 caused a 1.8 log10 (CFU/g) (CFU: Colony-Forming Unit) reduction of S. aureus in infected mouse thighs muscles and a downregulation of TNF-α, IL-6 and IL-10 levels, which were superior to those of DLP4 or vancomycin. These findings indicate that ID13 may be a promising peptide antimicrobial agent for therapeutic application.